Effects of Mangifera pajang Kostermans juice on plasma antioxidant status and liver and kidney function in normocholesterolemic subjects - Ibrahim, Muhammad; Ismail , Amin; Al-Sheraji, Sadeq Hassan; Azlan, Azrina; Abdul Hamid, Azizah (Elsevier, 2013)
The effects of a bambangan juice powder (BJP) drink on plasma vitamin and antioxidant enzyme levels and liver and kidney function were investigated. Thirty-two healthy subjects (12 male and 20 female) ages 24–28 years were recruited from the Faculty of Medicine and Health Sciences of University Putra Malaysia, Malaysia. Compared with consuming the placebo, consumption of the BJP drink daily for 9 weeks significantly increased the concentration of plasma b-carotene and ascorbic acid. Plasma total antioxidant status was increased, but liver and kidney functions were unaffected after consumption of the BJP drink. The consumption of a BJP drink resulted in a significant improvement in certain cardiovascular biochemical parameters and thus reduced the risk of cardiovascular disease.